Effectiveness of the Health Action Process Approach on Promoting the Health Behaviors of Male High School Students in Al-Rusafa District - jawad, fadhel (Iraqi National Journal of Nursing Specialties, 2022)
Objectives: The study aimed to evaluate health behavior, evaluate Health Action Process Approach, determine the effectiveness of the Health Action Process Approach based the application of program on students’ engaging in regular physical exercise.Methodology: The research design for this study was a quasi-experimental. The study sample included high school male students, the final sample size was(160 ) Non-probability sampling (convenience sample) are chosen, (80) students study group and (80) students control group.Results: The results show there was no statistically significant difference in the HAPA constructs among family's socioeconomic class groups and less than a half of participants in the study group that perform exercise regularly with longer interruptions. More than a half of participants in the study group they perform exercise during the week at least three times or more often for 30 minutes, to the extent of sweating (n = 41; 51.25) were compared to the control group (n = 31; 38.75%). There was a significant difference in the students' Motivational Self-Efficacy for exercising regularly, Coping Self-Efficacy for staying physically active, Smoking Outcomes Expectancies, and Anti-Smoking Self-Efficacy.Conclusions: The study concluded the Health Action Process Approach has positive effect on promoting health behavior, it is enhancing the study group students' motivation self-efficacy, coping self-efficacy for staying physically active.Recommendations: Based on the results of the present study the researcher recommends applying the health process approach to enhance students’ healthy behaviors.